PELIBATAN MASYARAKAT DENGAN PEMBERDAYAAN WARGA UNTUK MENCEGAH POTENSI PENYAKIT LEPTOSPIROSIS KELURAHAN KEBAGUSAN, JAKARTA SELATAN - Rina K Kusumaratna; BS Pribadi; DA Itami (Universitas Trisakti, 2021)
Leptospirosis is a zoonotic disease in sub-tropical and tropical climates, could develop into epidemics in both rural and urban areas. Leptospirosis usually occurs after the patient comes into after contact with flood. In the last 5 years the case of disease has increased in DKI Jakarta, as well as in the Kebagusan sub-district of South Jakarta which consists of 8 RWs, from 2017-2019 there were found 5 cases and potential for an epidemic at surrounding of neighborhood. Therefore, community engagement has a vital role to improve a disease prevention needs, thus those community are able to do an independently prevention activity or groups in their habitant. The activity begins with conducting an environment observational, advocacy and coordination, education and training for cadres, public facilities and infrastructure handling workers (PPSU) and residents representative of 3 RWs. From education results activities carried out on 36 targets, the pre-posttest on educated intervention was significant (p=0.000, T-paired test). It’s mean that the target increase their knowledge and understands the potential and risk of leptospirosis disease carried by rats for individual health and community after interventions. Empowerment can be started from the family level to maintain the cleanliness of the home environment as a form of personal responsibility and an important key to break the chain of leptospirosis transmission caused by rats